Localization of transcriptional regulatory elements and nuclear factor binding sites in mouse ribosomal protein gene rpL32. - Atchison, M L (1989)
The DNA sequences required for expression of the ribosomal protein gene rpL32 were identified by transient-expression assays of chimeric rpL32-chloramphenicol acetyltransferase genes. These studies showed that maximal rpL32 expression requires sequences in a 150- to 200-base-pair region spanning the transcriptional start site. Three discrete regions of importance were identified: one between positions -79 and -69 and two others located downstream of the transcriptional start site. Progressive 5' or 3' deletions caused stepwise decreases in expression, which suggested a complex interplay of redundant or compensatory elements. Gel mobility shift assays were used to identify trans-acting nuclear factors which bind to segments of the rpL32 promoter that are known to be important for transcription. Evidence for several distinct nuclear factors is presented. The binding sites for these factors were localized to the following regions: -79 to -69, -36 to -19, -19 to +11, +11 to +46 in exon I, and within the first 31 base pairs of intron 1. One of these factors may bind to multiple sites within the promoter region. Interestingly, the factor that binds to a sequence motif in the first exon also binds to similar motifs in a comparable region of the c-myc gene.